The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1186/s13046-016-0456-2
|View full text |Cite
|
Sign up to set email alerts
|

Use of poly ADP-ribose polymerase [PARP] inhibitors in cancer cells bearing DDR defects: the rationale for their inclusion in the clinic

Abstract: BackgroundDNA damage response (DDR) defects imply genomic instability and favor tumor progression but make the cells vulnerable to the pharmacological inhibition of the DNA repairing enzymes. Targeting cellular proteins like PARPs, which cooperate and complement molecular defects of the DDR process, induces a specific lethality in DDR defective cancer cells and represents an anti-cancer strategy. Normal cells can tolerate the DNA damage generated by PARP inhibition because of an efficient homologous recombinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
95
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(96 citation statements)
references
References 192 publications
0
95
0
Order By: Relevance
“…Frequent loss of several other genes involved in BRCA1-dependent homologous recombination (HR) repair has been demonstrated in basal-like/triple-negative cancer, most likely contributing to BRCA1-like features [17]. Due to innovative treatment options, information about the BRCA1-like or 'BRCAness' status may have important clinical implications: A number of studies have shown that homologous recombination deficiency (HRD) sensitizes the tumor to DNA-damaging agents such as platinum compounds, or to poly(ADP-ribose)polymerase (PARP) inhibitors, or their combination [18][19][20]. Accordingly, biomarkers to identify and select patients with BRCA1-like ('BRCAness') signatures are urgently required.…”
Section: Brca1-associated Tnbcmentioning
confidence: 99%
“…Frequent loss of several other genes involved in BRCA1-dependent homologous recombination (HR) repair has been demonstrated in basal-like/triple-negative cancer, most likely contributing to BRCA1-like features [17]. Due to innovative treatment options, information about the BRCA1-like or 'BRCAness' status may have important clinical implications: A number of studies have shown that homologous recombination deficiency (HRD) sensitizes the tumor to DNA-damaging agents such as platinum compounds, or to poly(ADP-ribose)polymerase (PARP) inhibitors, or their combination [18][19][20]. Accordingly, biomarkers to identify and select patients with BRCA1-like ('BRCAness') signatures are urgently required.…”
Section: Brca1-associated Tnbcmentioning
confidence: 99%
“…The lack of known specific molecular targets has led to extensive research to find possible vulnerabilities in TNBC. The biologic drugs already evaluated or under active research and that have shown antitumor activity in TNBC include angiogenesis inhibitors, PARP1 inhibitors, immune checkpoint inhibitors and AR antagonists, the latter used for the specific treatment of the luminal androgen receptor TNBC subtype that expresses high levels of AR (Lehmann et al 2015, Cerrato et al 2016, Hartkopf et al 2016. As a different approach, chemically modified taxanes have been, and are still, extensively being tested in clinical trials, alone or in combination with other chemotherapeutics.…”
Section: Amcd Use In Triple-negative Breast Cancer Therapy and Its Immentioning
confidence: 99%
“…Moreover, these are being extensively investigated in multiple clinical trials. PARP inhibitors are undergoing trials in different tumor types including ovarian, breast, pancreatic, gastric, non-small cell lung cancer, melanoma, glioblastoma, and other cancers [19].…”
Section: Therapeutic Significance Of Dna Mismatch Repair In Prostate mentioning
confidence: 99%